Experimental investigation on kinetic model with reaction heat for coal gasification in supercritical water. (15th May 2023) - Luo, Kui; Jin, Hui; Ou, Guobiao; Peng, Zhiyong; Sun, Jingli; Lu, Libo; Guo, Liejin
Highlights: Coal can be converted into hydrogen-rich gaseous products in SCW effectively. A reaction pathway combined with reaction heat determination was proposed. A method was developed to determine the reaction heat of each reaction. The reaction heat fluxes of the coal gasification process in SCW were quantified. Abstract: An accurate kinetic model, including the reaction pathway and reaction heat, is crucial to reactor scale-up and process optimization for the supercritical water gasification (SCWG) of coal. However, the reported kinetic models seldom satisfy the mass and energy conservation law due to the proposed inappropriate reaction pathway and difficult determination of reaction heat in supercritical water (SCW). This work focuses on determining the reaction heat and establishing a kinetic model based on mass and energy conservation law. A reaction pathway combined with reaction heat determination by a lumped method was proposed to establish a kinetic model and to quantify the reaction heat of each reaction in the coal gasification process. The steam reforming reaction I and II in the model have the highest activation energy, 59.629 ± 10.281 kJ/mol and 63.249 ± 3.937 kJ/mol, respectively. Reaction heats of the reaction between volatile and SCW and the steam reforming reactions exceed + 600 kJ/mol. Moreover, due to the combined influence of endothermic and exothermic reactions, the entire gasification process shift from endothermic to exothermic as the gasification proceeds. This work provides a more accurate mathematical model for the SCW reactor.